NSAIDs: how they work and their prospects as therapeutics in Alzheimer's disease - Sastre, Magdalena; Gentleman, Steve M. (Frontiers in Aging Neuroscience, 2010)
There is significant epidemiological evidence to suggest that there are beneficial effects of treatment with non-steroidal anti-inflammatory drugs (NSAIDs) in Alzheimer’s disease (AD), although these effects have not been reproduced in clinical trials. The failure of the clinical trials may be attributed to several possible facts: 1) NSAIDS may have been delivered too late to patients, as they may only be effective in early stages of the disease and possibly counterproductive in the late stages; 2) the beneficial effect may depend on the drug, because different NSAIDs may have different molecular targets; 3) the NSAID concentration reaching the brain and the duration of the treatment could also be critical, so increasing drug penetration is important in order to improve the efficacy and avoid secondary gastro-intestinal effects of the NSAIDs. In this report we analyse these different factors, with special emphasis on the role of NSAIDs in microglia activation over time.